Linguastylistic and Interpretative Features of English Military Slang Words in Unofficial Military Discourse (Proceedings of Southern Federal University. Philology, 2020)
This article is devoted to the analysis of military slang peculiarities. Military discourse is a topical issue in the context of modern military conflicts and military contacts development of the 21st century. Mentioned above discourse is the main instrument not only for giving commands and orders, strategies and doctrines, but it also aims at forming ideology in society, embracing the whole discourse. So communication in military circles and the discourse itself should transfer cultural models based on specific elements and phenomena. Army is known to be one of the most important social institutions of many governments including a complicated system of individuum relations realized by communication rules and regulations. Thus studying some peculiarities of military discourse verbalization as a social professional subcode is a really important issue. It emphasizes the applicability of this research.Key words: military discourse, slang, military subcultural linguistic worldimage, forms of slang formation.DOI 10.18522/1995-0640-2020-2-103-111